2014
DOI: 10.5387/fms.2013-14
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival After Resection of Metastases in the Lungs and Larynx Originating From Sigmoid Colon Cancer: Report of a Case

Abstract: : Metastatic neoplasms in the larynx from remote primary tumors are uncommon, and laryngeal metastasis originating from the colorectum is extremely rare. We herein report a case of metastatic laryngeal carcinoma originating from sigmoid colon cancer in a 54 -year -old female. Curative partial laryngectomy was performed, and the patient remains alive with a good quality of life and no signs of recurrence seven years and eight months after sigmoidectomy and four years and eight months after partial laryngectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…(3) The treatment modalities for secondary laryngeal metastasis vary depending on the stage of the disease, the number of the metastatic focus, and the involvement of other organs; in a case reported by Therasma et al in 2008, the laryngeal metastasis was managed with organ preservation surgery as the patient was in remission from his primary cancer with no other organ involvement. (7) Due to unfamiliarity with secondary laryngeal cancers, there is no census of the treatment guidelines; treatment options depend on the stage at the time of diagnosis, solitary laryngeal involvement, or the presence of other metastatic focus; however, it is thought that laryngeal cancer is still under-reported, as one postmortem study reported by Prescher et al showed laryngeal involvement in 6 autopsies out of 6 patients with prostate cancer and Horny and Kaiserling found 10 out of 14 patient with hematopoietic malignancy found to have laryngeal metastasis. (13,14) Incidental laryngeal metastasis without symptoms is also evident, as reported by Xia et al when a PET CT (positron emission tomography-computed scan) was done for an elevated AFP (Alfa fetoprotein) showed increased uptake in the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The treatment modalities for secondary laryngeal metastasis vary depending on the stage of the disease, the number of the metastatic focus, and the involvement of other organs; in a case reported by Therasma et al in 2008, the laryngeal metastasis was managed with organ preservation surgery as the patient was in remission from his primary cancer with no other organ involvement. (7) Due to unfamiliarity with secondary laryngeal cancers, there is no census of the treatment guidelines; treatment options depend on the stage at the time of diagnosis, solitary laryngeal involvement, or the presence of other metastatic focus; however, it is thought that laryngeal cancer is still under-reported, as one postmortem study reported by Prescher et al showed laryngeal involvement in 6 autopsies out of 6 patients with prostate cancer and Horny and Kaiserling found 10 out of 14 patient with hematopoietic malignancy found to have laryngeal metastasis. (13,14) Incidental laryngeal metastasis without symptoms is also evident, as reported by Xia et al when a PET CT (positron emission tomography-computed scan) was done for an elevated AFP (Alfa fetoprotein) showed increased uptake in the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…In 5 of these cases, the primary metastatic source was the sigmoid colon, in 1 the transverse colon, in 3 the right colon, in 1 only the cecum, and in 6 an unspecified colonic location. [2][3][4][5] This is the first clinical report of ileocecal valve and cecum adenocarcinoma metastatic to the larynx in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for laryngeal metastases are not well established, but males tend to have a greater predilection [1,10]. Secondary malignancies present with symptoms mimicking primary malignancies of the hypopharynx or larynx, including hoarseness, stridor, dyspnea, dysphagia, otalgia, and globus sensation [15][16][17]. Symptomatic patients may present early, but presentation is often delayed compared to primary laryngeal malignancies, especially if the lesion is submucosal [18].…”
Section: Discussionmentioning
confidence: 99%